Abortion liberalization demand in Argentina: legal discourses as site of power struggle A case study on the structural case Portal de Belen vs. Cordoba (2012-2013) - Monte, Maria Eugenia (2013)
Fil: Monte, María Eugenia. Universidad Nacional de Córdoba. Facultad de Derecho; Argentina.